A clash of heroes : Brandeis, Weizmann, and American Zionism - Halpern, Ben (Studies in Jewish history., 1987)
This book examines the conflict between Louis D. Brandeis and Chaim Weizmann, two heroes of a crucial era in recent Jewish history. The author considers how each man confronted the problem of his Jewish identity and the extent to which they both served as models for rival solutions.